2004
DOI: 10.1364/ao.43.002257
|View full text |Cite
|
Sign up to set email alerts
|

Mid-infrared quantum cascade laser based off-axis integrated cavity output spectroscopy for biogenic nitric oxide detection

Abstract: Tunable-laser absorption spectroscopy in the mid-IR spectral region is a sensitive analytical technique for trace-gas quantification. The detection of nitric oxide (NO) in exhaled breath is of particular interest in the diagnosis of lower-airway inflammation associated with a number of lung diseases and illnesses. A gas analyzer based on a continuous-wave mid-IR quantum cascade laser operating at approximately 5.2 microm and on off-axis integrated cavity output spectroscopy (ICOS) has been developed to measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
83
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(83 citation statements)
references
References 30 publications
0
83
0
Order By: Relevance
“…QCL-based systems, although still quite specialized, are finding applications in medical diagnostics [74]. Because they require relatively low power and are so small, QCL-based systems may eventually replace larger and slower FTIR and other spectroscopy systems for laboratory work and may thus, with further development, have a more applicable role in a clinical-based setting.…”
Section: Diabetesmentioning
confidence: 99%
“…QCL-based systems, although still quite specialized, are finding applications in medical diagnostics [74]. Because they require relatively low power and are so small, QCL-based systems may eventually replace larger and slower FTIR and other spectroscopy systems for laboratory work and may thus, with further development, have a more applicable role in a clinical-based setting.…”
Section: Diabetesmentioning
confidence: 99%
“…The OA-ICOS technique has been extensively reviewed in the literature [3][4][5][6][7][8]; here we briefly highlight the most relevant aspects. It is a laser-based spectroscopic method developed from cavity ring down spectroscopy.…”
Section: Oa-icosmentioning
confidence: 99%
“…The development of off-axis integrated cavity output spectroscopy (OA-ICOS) [3][4][5][6][7] offered mechanical robustness and relatively simple alignment for field measurements [8], being used in numerous studies during the recent years, such as isotopic studies [9,10] and breath analysis [4,11,12]. The method can straightforward be implemented into practical trace-gas detection schemes, offering great versatility and selectivity, making it less technically demanding and more cost effective than other laser-based methods.…”
Section: Introductionmentioning
confidence: 99%
“…Among the most valuable schemes, off-axis integrated-cavity-output spectroscopy (ICOS) offers several advantages. It combines the detection principle of cavity-enhanced absorption spectroscopy (CEAS) with a much simpler setup, using a multipasslike alignment for the high-finesse cavity [22][23][24][25][26]. Recently, Gupta et al have exactly reported absorption measurements of molecular hydrogen lines in Dicke-narrowing regime performed in the near infrared (8075 cm -1 ) by off-axis ICOS [27].…”
mentioning
confidence: 99%